THE EFFECT OF CRITICAL THINKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS COGNITIVE LEARNING THROUGH THINK PAIR SHARE (TPS) - Rika Yulita Sari; Undang Rosidin; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
An effective, efficient and attractive management in the learning process is the starting point for successful learning that will ultimately improve student achievement. To improve the quality of critical thinking and cognitive learning outcomes of students it is necessary to transform teaching, learning and changing components that can affect the learning process itself. This study aimed to determine the effect of critical thinking on cognitive learning outcomes of students with learning Think Pair Share. The research was conducted in Junior High School Wiyatama Bandar Lampung with a focus on legal research materials Newton. The research was conducted in January 2013. Type of research design one group pretest-posttest design. With purposive sampling. The research instrument used was a test instrument in the form of essay questions. Instrument test result data, analyzed by statistical tests such as test comparison of pretest and posttest critical thinking and cognitive outcomes. The results of data analysis found that there are differences in the ability of critical thinking and classroom learning outcomes significant results are based on the results of hypothesis testing using the T test for two values of N-gain. Results for the critical thinking skills As for the student learning outcomes is a significant value of 0.00. It shows that Ho refused and H1 accepted, it can be said that there was a significant effect of the average critical thinking skills and cognitive learning outcomes of students with learning using TPS.Keywords: Critical Thinking Skills, Learning Outcomes Physics, Model of Cooperative Learning, Think Pair Share (TPS).